2008
DOI: 10.1002/jpln.200700171
|View full text |Cite
|
Sign up to set email alerts
|

Pollutants in drainage channels following long‐term application of Mancozeb to banana plantations in southeastern Mexico

Abstract: The aim of this study was to investigate how long‐term Mancozeb application to banana plantations affects the occurrence of pollutants in drainage‐channel sediment and water under tropical conditions. We estimated the possible accumulation of Mancozeb's principal metabolite ethylenethiourea (ETU), as well as manganese (Mn) and zinc (Zn) as components in channel sediment and water. We took samples during the tropical‐rainfall season and the low‐rainfall season. For sediment samples, we determined the contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 10 publications
1
19
1
2
Order By: Relevance
“…The concentration of fungicide Tattoo [a commercial formulation containing 45% of propamocarb-HCl (propyl-3-(dimethylamino) propylcarbamate and 55% of mancozeb, or Zn, Mn ethylenebis(dithiocarbamate) [-SCSNH(CH 2 ) 2 NHCSSMn-]n(Zn) m(Mn)] used in this study was based on the higher limits of the ecologically relevant concentrations for fresh water (USEPA, 2005). The EU threshold value for drinking water for mancozeb's principal metabolite ethylenethiourea is 0.1 g L −1 , whereas its concentration in the agricultural drainage and runoff can reach 5.9-13.8 g L −1 (Melgar et al, 2008). It is worth noting that Tattoo contains Zn in low concentrations, and in the areas of the intensive application of Tattoo, elevated Zn concentrations were found in the sediment (87-190 mg kg −1 exceeding the threshold values for aquatic life of 98 mg kg −1 at several sites) (Melgar et al, 2008).…”
Section: Experimental Exposuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of fungicide Tattoo [a commercial formulation containing 45% of propamocarb-HCl (propyl-3-(dimethylamino) propylcarbamate and 55% of mancozeb, or Zn, Mn ethylenebis(dithiocarbamate) [-SCSNH(CH 2 ) 2 NHCSSMn-]n(Zn) m(Mn)] used in this study was based on the higher limits of the ecologically relevant concentrations for fresh water (USEPA, 2005). The EU threshold value for drinking water for mancozeb's principal metabolite ethylenethiourea is 0.1 g L −1 , whereas its concentration in the agricultural drainage and runoff can reach 5.9-13.8 g L −1 (Melgar et al, 2008). It is worth noting that Tattoo contains Zn in low concentrations, and in the areas of the intensive application of Tattoo, elevated Zn concentrations were found in the sediment (87-190 mg kg −1 exceeding the threshold values for aquatic life of 98 mg kg −1 at several sites) (Melgar et al, 2008).…”
Section: Experimental Exposuresmentioning
confidence: 99%
“…The EU threshold value for drinking water for mancozeb's principal metabolite ethylenethiourea is 0.1 g L −1 , whereas its concentration in the agricultural drainage and runoff can reach 5.9-13.8 g L −1 (Melgar et al, 2008). It is worth noting that Tattoo contains Zn in low concentrations, and in the areas of the intensive application of Tattoo, elevated Zn concentrations were found in the sediment (87-190 mg kg −1 exceeding the threshold values for aquatic life of 98 mg kg −1 at several sites) (Melgar et al, 2008).…”
Section: Experimental Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Within our study area, we found some indications of humaninduced mortality in Malay civets; for instance, within the plantation we found the remains of a radio-collar that had clearly been cut off from one female (F3). Other likely threats to this species include pesticides that are applied in plantations; these contaminate groundwater systems and carnivore prey (through bioaccumulation), which can eventually lead to adverse health problems in carnivore species that forage in these areas (Elliott et al, 1999;Melgar et al, 2008).…”
Section: Habitat Use and Conservationmentioning
confidence: 99%
“…Contaminated environmental systems and threatened food safety, the unexpected consequences of pesticide application, however, have become worldwide issues in recent decades (Geissen et al, 2010;Richards and Baker, 1993;Ruiz-Suarez et al, 2014). Pesticides applied to farmland can accumulate onsite or be transported offsite during the process of decay (Glotfelty et al, 1984;Melgar et al, 2008;Ongley et al, 2010). Pesticide registration, production, and application are thus supervised and even restricted based on the physicochemical properties, i.e.…”
Section: Introductionmentioning
confidence: 99%